2016
DOI: 10.14202/vetworld.2016.1331-1337
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Gamma-hexachlorocyclohexane (Lindane) induced renal toxicity by Camellia sinensis in Wistar rats

Abstract: Aim:A study to assess the toxic effects of gamma-hexachlorocyclohexane (γ-HCH) (lindane) and ameliorative effects of Camellia sinensis on renal system has been carried out in male Wistar rats.Materials and Methods:Four groups of rats with 18 each were maintained under standard laboratory hygienic conditions and provided feed and water ad libitum. γ-HCH was gavaged at 20 mg/kg b.wt. using olive oil as vehicle to Groups II. C. sinensis at 100 mg/kg b.wt. was administered orally in distilled water to Group IV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The daily administration of black tea induced diuresis, an effect accompanied by increased urine levels of Na + . Prasad et al [38] . evaluated the effect of the methanolic extract of C. sinensis leaves to improve the renal toxicity induced by gamma‐hexachlorocyclohexane in NTR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily administration of black tea induced diuresis, an effect accompanied by increased urine levels of Na + . Prasad et al [38] . evaluated the effect of the methanolic extract of C. sinensis leaves to improve the renal toxicity induced by gamma‐hexachlorocyclohexane in NTR.…”
Section: Resultsmentioning
confidence: 99%
“…The daily administration of black tea induced diuresis, an effect accompanied by increased urine levels of Na + . Prasad et al [38] evaluated the effect of the methanolic extract of C. sinensis leaves to improve the renal toxicity induced by gamma-hexachlorocyclohexane in NTR. That study suggested that the extract of C. sinensis, combined with the toxic agent, reduced oxidative stress generation, toxicity, and kidney tissue damage.…”
Section: Camellia Sinensis L Kuntzementioning
confidence: 99%
“…The health-related benefits of CO in previous paper are centered on urinary disease ( Prasad, Srilatha, Sailaja, Raju, & Jayasree, 2016 ; Zeng et al, 2020 ), cardiovascular system disease ( Huang et al, 2023 ; H. Shi, Zhou, He, Wang, & Zhou, 2022 ), nervous system disease ( Guo et al, 2022 ; Weng, Chen, Li, & Yen, 2020 ) and digestive system disease ( Cheng et al, 2014 ; Lee, Tung, Wu, Tu, & Yen, 2018 ; Wang, Tung, Chen, Lee, & Yen, 2019 ) ( Fig. 5 A).…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 5 (A) The main systemic diseases associated with CO. [1] ( Zeng et al, 2020 ), [2] ( Prasad et al, 2016 ), [3] ( Guo et al, 2022 ), [4] ( Weng et al, 2020 ), [5] (H. Shi et al, 2022 ), [6] ( Huang et al, 2023 ), [7] ( Cheng et al, 2014 ), [8] ( Wang et al, 2019 ), [9] ( Lee et al, 2018 ). (B) Pharmacological maps of the network related to differential AIs under insect stress.
…”
Section: Discussionmentioning
confidence: 99%
“…Several plant species have medicinal value with great antioxidant potency (Krishnaiah, Sarbatly, & Nithyanandam, 2011), like black tea (BTE) (Łuczaj & Skrzydlewska, 2005) and curcumin (CMN) (Zhang et al., 2016). BTE derived from Camellia sinensis , was used as antioxidant (Raihan et al., 2009) for its polyphenols constituents (Jha, Krithika, Manjeet, & Verma, 2013), it was found to reduce the thiobarbituric acid reactive substance (TBARS) elevated in AFB1‐renal intoxication (Choudhary & Verma, 2006), and also normalize the elevated creatinine, urea, and uric acid in blood as a result of other toxic factors like lindane (Prasad, Srilatha, Sailaja, Raju, & Jayasree, 2016). Furthermore, CMN is the major component of turmeric (Menon & Sudheer, 2007), it is derived from Curcuma longa Linn (Zingiberaceae family) rhizomes, and used as antimutagenic, anti‐inflammatory, anticancer, and antioxidant (Duvoix et al., 2005; Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%